Climate Change Epistemologies in Southern Africa Social and Cultural Dimensions - Ahrens, Jörn; Halbmayer, Ernst (Routledge Studies in African Geography, 2023)
This book investigates the social and cultural dimensions of climate change in Southern Africa, focusing on how knowledge about climate change is conceived and conveyed. Despite contributing very little to the global production of emissions, the African continent looks set to be the hardest hit by climate change. Adopting a decolonial perspective, this book argues that knowledge and discourse about climate change has largely disregarded African epistemologies, leading to inequalities in knowledge systems. Only by considering regionally specific forms of conceptualizing, perceiving, and responding to climate change can these global problems be tackled. First exploring African epistemologies of climate change, the book then goes on to the social impacts of climate change, matters of climate justice, and finally institutional change and adaptation. Providing important insights into the social and cultural perception and communication of climate change in Africa, this book will be of interest to researchers from across the fields of African studies, sociology, anthropology, philosophy, political science, climate change, and geography.